2019
DOI: 10.1128/mbio.01319-19
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquinone Biosynthesis over the Entire O 2 Range: Characterization of a Conserved O 2 -Independent Pathway

Abstract: Most bacteria can generate ATP by respiratory metabolism, in which electrons are shuttled from reduced substrates to terminal electron acceptors, via quinone molecules like ubiquinone. Dioxygen (O2) is the terminal electron acceptor of aerobic respiration and serves as a co-substrate in the biosynthesis of ubiquinone. Here, we characterize a novel, O2-independent pathway for the biosynthesis of ubiquinone. This pathway relies on three proteins, UbiT (YhbT), UbiU (YhbU), and UbiV (YhbV). UbiT contains an SCP2 l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 80 publications
(119 reference statements)
2
54
0
Order By: Relevance
“…The nrdD gene codes for anaerobic ribonucleoside triphosphate reductase, which is essential in E. coli for deoxyribonucleotide synthesis during strict anaerobic growth ( Garriga et al, 1996 ). ubiQ is required for anaerobic ubiquinone biosynthesis ( Pelosi et al, 2019 ). GrcA restores pyruvate formate-lyase (PFL) activity after oxidative damage to the main PFL subunit ( Wagner et al, 2001 ; Bowman et al, 2019 ) and thus may help the pathogen to maintain the high activity of key glycolysis enzyme at microaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The nrdD gene codes for anaerobic ribonucleoside triphosphate reductase, which is essential in E. coli for deoxyribonucleotide synthesis during strict anaerobic growth ( Garriga et al, 1996 ). ubiQ is required for anaerobic ubiquinone biosynthesis ( Pelosi et al, 2019 ). GrcA restores pyruvate formate-lyase (PFL) activity after oxidative damage to the main PFL subunit ( Wagner et al, 2001 ; Bowman et al, 2019 ) and thus may help the pathogen to maintain the high activity of key glycolysis enzyme at microaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes of this category include moeB (SGRAN_0222), an unlinked gene involved in Mo cofactor biosynthesis, most of the components of the cyoABCDEregBA operon, (SGRAN_2997-_2991) encoding a bo3 -type quinol oxidase electron transfer chain and the redox responsive regBA two-component regulatory system 18 . yhbTUV operon (SGRAN_3858-_3860) is one of the most induced operons in anaerobiosis 17 and it is involved in the recently described O 2 -independent ubiquinone biosynthesis pathway, proposed to be renamed ubiTUV 35 , and it is essential for denitrification in Pseudomonas 36 . Althought dRNA-Seq showed that expression of the distal genes of this operon was still maintained to some extent in the Δ narG mutant, the , induction kinetics of ubiU in Δ fnr and in Δ narG mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an iron-sulfur cluster might be another feature common to U32 proteins. Indeed, we showed that UbiU and UbiV each carry a 4Fe-4S cluster ligated by a motif of conserved cysteine residues, which is found in most U32 peptidase family members 46 . Interestingly, the function of RlhA and TrhP depends on these Cys residues and on the genes of the isc operon that catalyze the biogenesis of Fe-S clusters 57,59 .…”
Section: Discovery Of a Conserved O2-independent Pathwaymentioning
confidence: 97%
“…Based on the observation that E. coli was able to synthesize UQ under anoxic conditions, the existence of a UQ biosynthesis pathway independent from O2 had long been hypothesized 55 . This pathway remained uncharacterized until 2019, when we identified three genes, ubiT, ubiU and ubiV which are required for UQ biosynthesis under anoxic conditions but are dispensable under oxic conditions 46 we also hypothesized that UbiU and UbiV may participate in the two other hydroxylation steps of the anaerobic UQ pathway, thus substituting for UbiI and UbiH of the O2-dependent pathway (Figure 3A) 46,56 .…”
Section: Discovery Of a Conserved O2-independent Pathwaymentioning
confidence: 98%
See 1 more Smart Citation